2018
DOI: 10.1186/s13071-018-2994-2
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of Ixodidae ticks on privately owned dogs in Italy

Abstract: BackgroundThe geographical distribution of ticks on companion animals needs to be monitored to develop and plan effective control measures, as suggested by the European Scientific Counsel on Companion Animal Parasites. The aim of this study was to conduct the first Italian national survey of tick distribution on privately owned dogs.MethodsThe study was performed over 20 months (February 2016 - September 2017) and involved 153 veterinary practices in 64 different provinces covering 17/20 (85%) Italian regions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 39 publications
(56 reference statements)
4
39
2
Order By: Relevance
“…These two tick species often parasitize wild carnivores in Romania (D’ Amico et al ). In Italy, coinfestation with two different tick species was found in 1.7% of examined dogs (Maurelli et al ) and in Greece on 6.7% of dogs (Latrofa et al ), while in this study we found coinfestation on 13.3% of dogs. Most of the coinfested animals were parasitized by D. reticulatus in association with D. marginatus , H. inermis, and I. ricinus .…”
Section: Discussioncontrasting
confidence: 46%
“…These two tick species often parasitize wild carnivores in Romania (D’ Amico et al ). In Italy, coinfestation with two different tick species was found in 1.7% of examined dogs (Maurelli et al ) and in Greece on 6.7% of dogs (Latrofa et al ), while in this study we found coinfestation on 13.3% of dogs. Most of the coinfested animals were parasitized by D. reticulatus in association with D. marginatus , H. inermis, and I. ricinus .…”
Section: Discussioncontrasting
confidence: 46%
“…Moreover, the detection of B. vulpes DNA in unfed Dermacentor reticulatus ticks in Austria (53) may suggest a possible role of this tick species as well. In the study area, both I. hexagonus and D. reticulatus have been described infesting privately owned dogs (54).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only Rhipicephalus turanicus has been considered as an additional definitive host for this parasite (60), while Dermacentor spp., Haemaphysalis concinna and Ixodes ricinus have proved to harbor parasite DNA (35,61). In Northern Italy, both the proved and the suspected vectors of H. canis have been reported in dogs (54) and humans (62). Predation has been proved to be an alternative route for Hepatozoon americanum infection, a closely related species endemic in the United States (63), thus suggesting a similar transmission way for H. canis.…”
Section: Discussionmentioning
confidence: 99%
“…When pets like domestic dogs are involved, they are perceived by public opinion as a significant threat to both animal and human health [4,7,8]. Protozoa of the genera Babesia/Theileria were detected in 27.6% of the examined tick pools, with a higher prevalence in I. ricinus, which is the second most frequently reported tick affecting Italian dogs [23]. [45].…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, several efforts have been made to evaluate the prevalence of circulating tick-borne pathogens in ticks collected from dogs [21,22], although limited to certain areas. In order to better understand the distribution of TBPs in Italy, we propose the first large-scale molecular survey on TBPs harbored in ticks collected from privately-owned dogs [23]. We selected as target TBPs protozoa of the genera Babesia and Theileria, bacteria belonging to the family Anaplasmataceae and to the Borrelia burgdorferi s.l.…”
Section: Introductionmentioning
confidence: 99%